Pengaruh Laba, Arus Kas Dan Corporate Governance Terhadap Financial Distress (Studi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2011-2015) - septy indra santoso (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2017)
This study aimed to examine the effect of earnings, cash flow and corporate governance on financial distress. The corporate governance in this study using the indicator managerial ownership, institutional ownership and the board size. The population in this of the manufacturing companies listed on Indonesia Stock Exchange at the period of 2011-2015. Based on the criteria purposive sampling method, samples obtained is 28 companies in period 2011-2015 so obtain 140 observations. This study used logistic regression analysis. The result of this research showed that manajerial ownership has a positive effect and the board size have negative effect on the financial distress condition. This research failed to does not effect of the earnings, cash flow and institutional ownership of the financial distress condition.